Effect of Glyphosate and Zinc Application on Yield, Soil Fertility, Yield Components, and Nutritional Status of Soybean - Moreira, A.; Moraes, L. A.C.; Furlan, T.; Heinrichs, R. [UNESP] (Taylor & Francis, 2016)
Glyphosate is a widely used nonselective herbicide for the control of agricultural weeds. It is being increasingly used in glyphosate resistant genetically modified plants. However, there are few studies on its effects on the nutritional status of soybean, particularly on the uptake of zinc (Zn). Two experiments were conducted under field conditions in a Typic Quartzipsamment and an Orthic Ferralsol to investigate the effect of glyphosate application × Zn interaction on soil fertility, yield components, seed yield (SY), shoot dry weight (SDW) yield, and nutritional status of soybean. The five Zn rates 0, 3, 6, 9, and 12 kg ha−1 were used in two soybean varieties [BRS 133 (conventional—NGM) and its essentially derived transgenic line BRS 245RR (GM), which was divided into: with (+Gly) and without (–Gly) glyphosate application. Only the P (phosphorus) and Zn available concentrations in the soil were impacted by Zn rates. However, the available P concentration only decreased in the soil planted with GM soybean. Mehlich 1 and diethylenetriaminepenta acetic acid–triethanolamine (DTPA–TEA), 7.3 extractants were effective to determine the available Zn. In the two crop sites, the number of pods per plant (NPP) and the SDW yield were affected by the interaction varieties × Zn. SY was influenced by the application of the herbicide, reducing a potential phytotoxic effect with the use of high rates. Regarding the nutrients, only the foliar calcium (Ca), boron (B), iron (Fe), and manganese (Mn) concentrations were negatively affected by glyphosate, and in the case of Zn, the difference occurred only between the varieties BRS 133 and BRS 245RR.
Keywords: Acid soils; effect of the herbicide; Glycine max; uptake of nutrients; Zn extractants